Eating behaviour associated with differences in conflict adaptation for food pictures. (1st October 2016) - Husted, Margaret; Banks, Adrian P.; Seiss, Ellen
Abstract: Objective: The goal conflict model of eating (Stroebe, Mensink, Aarts, Schut, & Kruglanski, 2008) proposes differences in eating behaviour result from peoples' experience of holding conflicting goals of eating enjoyment and weight maintenance. However, little is understood about the relationship between eating behaviour and the cognitive processes involved in conflict. This study aims to investigate associations between eating behaviour traits and cognitive conflict processes, specifically the application of cognitive control when processing distracting food pictures. Method: A flanker task using food and non-food pictures was used to examine individual differences in conflict adaptation. Participants responded to target pictures whilst ignoring distracting flanking pictures. Individual differences in eating behaviour traits, attention towards target pictures, and ability to apply cognitive control through adaptation to conflicting picture trials were analysed. Results: Increased levels of external and emotional eating were related to slower responses to food pictures indicating food target avoidance. All participants showed greater distraction by food compared to non-food pictures. Of particular significance, increased levels of emotional eating were associated with greater conflict adaptation for conflicting food pictures only. Conclusion: Emotional eaters demonstrate greater application of cognitive control for conflicting food pictures as part of a food avoidance strategy. This could represent an attempt to inhibit their eating enjoyment goal in order for their weight maintenance goal to dominate.